From sustainability to self-sustainability: considerations on the eco-territorialist proposal - Ferreri, Fabrizio (Scienze del Territorio, 2022)
In the transition from sustainability to self-sustainability, which corresponds to the revision of the notion of environment in the direction of the concept of territory, it is possible to highlight the epistemological turning point of eco-territorial proposal. The environmental and ecological issue requires a holistic consideration, in the synthesis between theory and practice, capable of reaffirming a new subjectivity of the territory within the framework of an 'other' development compared to the dominant neoliberal model. 'Return to the territory' and 'place awareness' are welded together for a territorial ecology, not simply defensive, which questions in depth the generative rules of the relationship between man and territory in order to restore place-based social, cultural and economic forms of life.